The construct of career success: Measurement issues and an empirical example. - Abele, Andrea E.; Spurk, Daniel; Volmer, Judith (Journal for labour market research, 2011)
The aim of the present paper is twofold. We first give an overview of the multi-faceted construct of career success with its “objective” (real attainments) and “sub- jective” (perceived attainments) components and with the different methodologies measuring them (“subjectivist” vs. “objectivist” approaches). We also discuss the relationship between the different components of career success as revealed in the literature. Our second aim is to show that the interrelationship between the different facets of career success varies with the emplo yment context. We analyze subjective and objective career success measures collected from professionals working either in the private sector, in the public sector, or that are self-employed. Our findings show that objective success and subjective success are more closely related in the private and self-employment sectors than in the public sector. Moreover, the interrelationship between objective and subjective success varies with the specific subjective success measure chosen. It is stronger for an “other-referent” subj ective success measure than for a “self-referent” subjective s uccess measure. Conclusions regarding the measurement of career success as well as regarding the relevance of subjective success for studying occupational careers are drawn
Keywords: Objective vs. subjective career success; Self-referent vs. other-re ferent subjective success; Interplay between objectiv e and subjective success in different fields of employment